Implementasi Ketahanan Pangan Urban Farming dengan Penanaman Ubi Jalar dalam Karung - Hidayati, Nurul; Rosawanti, Pienyani; Susilo, Djoko Eko Hadi; Arfianto, Fahruddin; Hariyadi, Hariyadi (Daun: Jurnal Ilmiah Pertanian dan Kehutanan, 2024)
This study explores the implementation of urban farming techniques such as vertical gardening, hydroponics, tabulapot, and the cultivation of food plants in sacks and planters in urban areas. With a focus on household food security, sweet potato was selected as the crop due to its ease of growth and adaptability to various environmental conditions. Additionally, sweet potatoes can be successfully cultivated in sacks. The yield includes both tubers and leaves, which can be consumed as healthy vegetables.The primary objective of this research was to analyze the productivity of sweet potatoe s grown in sacks, and to examine the relationship between harvest variables and yield prediction. An experimental and descriptive research methodology was employed. Regression correlation analysis was conducted to determine the relationship between the number of tubers and the total weight per sack, as well as to estimate the potential yield.The results indicated a sweet potato productivity of 1.4 kg per 40 kg sack, with 10 cuttings per sack. A strong positive correlation of 96.77% was found between the number of tubers and the total tuber weight per sack, represented by the regression equation y= 71.069x-878.93. Similarly, a strong positive correlation of 83.05% existed between the number of tubers and the weight of each tuber, suggesting that an increasednumber of tubers did not decrease the weight of individual tubers, as shown by the regression equation y=1.6985x -9.87. If a household has 10 sacks, the potential yield would be 14,000 grams or 14 kg of sweet potatoes, providing a valuable source of healthy vegetables for the family.